An examination of the role of autonomous versus controlled motivation in predicting inpatient treatment outcome for anorexia nervosa. Issue 6 (3rd February 2016) - Thaler, Lea; Israel, Mimi; Antunes, Juliana Mazanek; Sarin, Sabina; Zuroff, David C.; Steiger, Howard
ABSTRACT: Objective: We explored the effect of autonomous and controlled motivation on outcomes for patients undergoing inpatient treatment for Anorexia Nervosa (AN). Method: Data on 80 patients with AN were available for the start of treatment, and for 49 at end of treatment. Patients completed measures of autonomous and controlled motivation, eating disorder symptoms and attitudes, and comorbid psychopathology at the start and end of treatment. Results: Patients showed significant improvements on eating symptoms and comorbid psychopathology over the course of treatment. Autonomous motivation was a significant predictor of change in severity of eating symptoms and attitudes such that patients with higher pre‐treatment levels of autonomous motivation showed larger post‐treatment reductions on these indices. No such effects were associated with controlled motivation. Discussion: This study highlights a relationship between autonomous motivation and outcome in an inpatient setting. © 2016 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:626–629)